PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN PENERAPAN MODEL DISCOVERY LEARNING MENGGUNAKAN KONTEKS BUDAYA MELAYU PADA MATERI BARISAN DAN DERET KELAS XI - Hasniati, Amalia; Murni, Atma; Siregar, Syarifah Siregar Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to produce learning devices by discovery learning model using cultural context of Malay on Sequence and Series material of class XI. The study model used is 4-D that consist of define, design, develop, and disseminate. The research instrument used is validity device and practicality device. The validity device is a validation sheets to assess the feasibility learning devices form of syllabus, lesson plan (RPP), and student worksheets (LKPD). The practicality device is practically sheets towards use student worksheets. The learning devices developed are validated by three validators. The research trials were conducted in SMAN 15 Pekanbaru which is tested in a small group and large group. Based on the data analysis, it can be conclude that the average value for syllabus, lesson plan, dan student worksheets are 3.61; 3.53; and 3.54 that are in very valid category. The student worksheets valued as very practical with mean score for small group and large group testing are 3.45 and 3.39 that are in very practical category. This Research and Deveplopment aims to produce learning devices by discovery learning model using cultural context of Malay on Sequence and Series material of class XI in high school consist of valid for syllabus and lesson plan, and then valid too practical for student worksheets.Key Words: Learning Devices, Discovery Learning Model, Cultural Contex of Melayu, Development Research, 4-D Model